TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN PADA SUMMARECON BANDUNG MENURUT UNDANG-UNDANG NO 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS: Corporate Social And Environmental Responsibility Of The Company Summarecon Bandung According To Law No 40/2007 Concerning Companies - Jihan Syafira; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2026)
Summarecon Bandung is a company that operates in the property development sector. As a company, Summarecon Bandung is obliged to implement the company's TJSL in accordance with Law Number 40 of 2007 concerning Limited Liability Companies. Provisions regarding TJSL are regulated in Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies. The problem of this research is what are the obstacles to the Implementation of Social and Environmental Responsibility (TJSL) Summarecon Bandung. The author in this research used a normative approach, descriptive in nature and analyzed qualitatively. The results and conclusion of the discussion of the obstacles to implementing TJSL at Summarecon Bandung occurred in two stages, namely the planning stage, problems with inappropriate data distribution when the program was implemented and the implementation stage, problems with communication where when making a program for one group, other groups felt neglected.